Paradigma Integralistik Agama dan Negara : Studi Kritis Pemikiran Politik Abū A’lā Al-Maudūdī - Taufiqul Hadi; Ginting, Amru (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2023)
Discourse on religious and state relations is increasingly developing among Muslim thinker, one of them is a paradigm that integrates religion and the state. Abū A'lā al-Maudūdī is known for the idea of theo-democracy which is based on an understanding of the teachings of monotheism. This article aims to find out how al-Maudūdī's Islamic political thought plays out in contemporary political dynamics, especially in the discourse on relations between religion and the state. This research is library research with the nature of qualitative research which has the main characteristics of descriptive interpretive. The results of the research show that the integralism of religion and state carried out by al-Maudūdī wants a universal Islamic state using a theo-democratic system, where the Islamic state uses the Koran and Sunnah as the basis of state law and complete submission to God's sovereignty and does not justify the sovereignty of the people. Al-Maudūdī's political ideas can be considered controversial and irrelevant when connected to political realities in the modern era.